2009
DOI: 10.1007/s11430-009-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate changes in East China since the Late-glacial inferred from high-resolution mountain peat humification records

Abstract: High-resolution peat humification records were obtained from Dajiuhu of the Shennongjia Mountains and Qianmutian of the Tianmu Mountains to study climate changes in EastChina. The analyses of pollen, organic matters, TOC, and Rb/Sr indicate a high degree of peat humification and thus strong decomposition of organic matter when climate was dry. Conversely, when climate was humid, the degree of humification is low because peat was preserved in a waterlogged condition. Peat humification from Dajiuhu occurred not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…The Paleoclimate Modeling Intercomparison Project (PMIP) reported the results of 18 models that showed that amplification of the northern hemispheric seasonal cycle of insolation during the mid-Holocene, specifically at 6 ka, caused a northward shift in monsoon precipitation (Joussaume et al, 1999). A well-dated peat core from Dajiuhu Lake located 125 km north of Heshang Cave (at 31.49 • N, 109.99 • E, 1760 m), has been studied extensively using a variety of paleoclimate proxies including pollen (Zhu et al, 2006(Zhu et al, , 2010Chen et al, 2008;Zhao and Chen, 2010), minerogenic matter (Zhu et al, 2010), total organic carbon , and degree of humification (Ma et al, 2009). All proxies from the Dajiuhu peat core show the same general trend of gradually increasing summer monsoon strength from the Late-glacial interval to 6 ka, with interruptions at the Younger Dryas and 8.2 ka event.…”
Section: Climatic Influences On Dcp During the Mid-holocenementioning
confidence: 99%
“…The Paleoclimate Modeling Intercomparison Project (PMIP) reported the results of 18 models that showed that amplification of the northern hemispheric seasonal cycle of insolation during the mid-Holocene, specifically at 6 ka, caused a northward shift in monsoon precipitation (Joussaume et al, 1999). A well-dated peat core from Dajiuhu Lake located 125 km north of Heshang Cave (at 31.49 • N, 109.99 • E, 1760 m), has been studied extensively using a variety of paleoclimate proxies including pollen (Zhu et al, 2006(Zhu et al, , 2010Chen et al, 2008;Zhao and Chen, 2010), minerogenic matter (Zhu et al, 2010), total organic carbon , and degree of humification (Ma et al, 2009). All proxies from the Dajiuhu peat core show the same general trend of gradually increasing summer monsoon strength from the Late-glacial interval to 6 ka, with interruptions at the Younger Dryas and 8.2 ka event.…”
Section: Climatic Influences On Dcp During the Mid-holocenementioning
confidence: 99%
“…Although the first description of peat was in the "Diary of the Travels of Xu Xiake" more than 400 years ago, the study of peat records of paleoclimate in China has lagged until recently, developing fast over the last 20 years (Xie et al 2000;Zhou et al 2001Zhou et al , 2002aZhou et al , b, 2004Zhou et al , 2005Zhou et al , 2007Zhou et al , 2010aHong et al 2000Hong et al , 2001Hong et al , 2003Hong et al , 2005Hong et al , 2009Hong et al 2010;Yu et al 2006bYu et al , 2011Wang et al 2004c;Zheng et al 2009aZheng et al , b, 2011aZhu et al 2009;Ma et al 2009;Yu and Liu 2010;Zhong et al 2010a, b). Paleoclimate reconstructions have focused on the monsoonal region.…”
Section: Peat Localities and Paleoclimatic Implicationsmentioning
confidence: 99%
“…Plant macrofossils (Barber et al, 2000;Barber et al, 2003;Väliranta et al, 2007; and peat humification (Mauquoy and Barber, 1999;Chiverrell, 2001;Ma et al, 2009) have been used as indicators of vegetation and peatland surface wetness. Owing to their characteristics, such as size and weight, plant macrofossils represent the historic vegetation of peat sediments in situ (Birks, 2002;Mauquoy and Van Geel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As an indicator of the degree of peat decomposition, peat humification has been thought to represent the environmental conditions at the time of peat accumulation, especially for surface wetness (Chambers et al, 2012). Studies of peat humification recently began in China and presented key information about environmental changes during the Holocene (Ma et al, 2009;Ma, 2010). Analysis of peatland plant macrofossils could be used to reconstruct peatland vegetation history and determine the successional process of peatlands (Jasinski et al, 1998;Branch et al, 2012;Pawlowski et al, 2012;Galka and Sznel, 2013), reconstruct peatland surface wetness (Väliranta et al, 2007;Mauquoy et al, 2008;Galka and Apolinarska, 2014;Zhao et al, 2014), and distinguish between the relative influence of climate change and human disturbance on the process of peatland development (Chambers et al, 2007a;2007b;Tuittila et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation